2015
DOI: 10.1111/cyt.12260
|View full text |Cite
|
Sign up to set email alerts
|

Does LLETZ excision margin status predict residual disease in women who have undergone post‐treatment cervical cytology and high‐risk human papillomavirus testing?

Abstract: TOC pathways recommend subsequent follow-up in primary care. This study identified no safety issues with TOC pathways. We can no longer assess histological failure rates at 12 months; we, therefore, recommend that this measure of treatment failure be redefined for post TOC women. It seems time to question the benefits of routine excision margins reporting, in the absence of invasion, for treated CIN. Future reporting needs to be reconsidered by the Royal College of Pathologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
5
10
0
Order By: Relevance
“…The findings of the present study showed that the percentage of disease persistence at 6 months after LLETZ was 19.9%, which is in line with 20.0% showed by Palmer et al 16 After 12-18 months, we found a rate of 12.8% for disease persistence, similar to those provided by F I G U R E 1 Microscope measuring process of the conization depth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study showed that the percentage of disease persistence at 6 months after LLETZ was 19.9%, which is in line with 20.0% showed by Palmer et al 16 After 12-18 months, we found a rate of 12.8% for disease persistence, similar to those provided by F I G U R E 1 Microscope measuring process of the conization depth.…”
Section: Discussionsupporting
confidence: 92%
“…This was in contrast to the findings of Zhu et al, 17 The present study showed that 12.5% of the endocervical margin was affected, which is significantly lower than the 24.1% described by Venegas-Rodríguez et al 18 In the present study, the affected endocervical margin was found to be a risk factor for pathological cytology presenting at 6 months post-treatment, which increased the risk by three times compared to the non-affected endocervical margin. 2 The affected endocervical margin was also shown to be a risk factor for HPV persistence after 6 months, in agreement with the findings of Sarian et al, 27 but in contrast with Palmer et al 16 who did not find a correlation between affected margins and HPV status. 21,22 However, the endocervical margin was not identified as a risk factor for the 12-18 month group, which may be due to the tendency of the lesion to return, as indicated by Chikazawa et al 2 This regression was possibly caused by the inflammation and healing process that takes place after conization, which is more frequent 6 months after conization and, in most cases, occurs within the first 12 months.…”
supporting
confidence: 83%
“…Palmer et al . also questioned the rule of reporting the margins of excision in the absence of invasion and/or CGIN in the histology results when the TOC is used for patients treated for CIN . The present findings support Palmer et al.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study assessing the correlation between margins of excision and hrHPV status at TOC among women treated for CIN has suggested that incomplete excision of margins is neither one of the main factors associated with treatment failure nor an indication for further surgical intervention . Palmer et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation